The Resiliency of Islamic Boarding Schools in the Covid-19 Pandemic Era - Buchori, Imam; Junjunan, Mochammad Ilyas; Nawangsari, Ajeng Tita (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study focuses on the administrative leadership, financial oversight, and instructional practices of the boarding schools al-Amanah Junwangi, Manba'ul Hikam Putat, and Annur Penatarsewu, Sidoarjo. This study employed a quantitative approach and a case study methodology. Respondents who served as informants for the study included KH. Nurcholis Misbah from al-Amanah, KH. Muh. Salim Imron from Manba'ul Hikam, and KH. Anwar Ichsan from Annur. To give more pertinent supporting information, additional respondents were also included. The findings of this study include Islamic boarding schools applying various learning patterns, ranging from full online, hybrid class systems, to face-to-face by maintaining distance. Additionally, al-Amanah and Manba'ul Hikam were not as negatively impacted financially because the two boarding schools had sufficient "reservoirs" that could accommodate all activities that caused costs to arise during the pandemic and strong confidence and resolve to face the pandemic. In contrast, Annur Islamic boarding school had sufficient impacts on learning and financial management. The fact that Annur Islamic Boarding School has several alumni who support the academic success of students who are impacted by the moving learning model, however, is another strength that has helped it survive during the COVID-19 pandemic.